The Spectrum of Inerrancy: An Exploration of David S. Dockery’s Typological Contributions to the Inerrancy Debate in Evangelicalism - DESJARDINS, Gabriel A. (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2021)
The present article explores the typological contributions to the inerrancy debate of David S. Dockery, the Chancellor of Trinity International University. Resulting from controversies in the Southern Baptist Convention (SBC) during the 1970s and 80s, Dockery provided a valuable typological framework for iden-tifying a spectrum of positions in the inerrancy debate. Dockery’s frameworks provide a helpful lens for understanding the complexity of inerrancy. Some posi-tions are more conservative and deductivist, and other positions are more liberal and inductivist. These distinctions often create a barrier, a presuppositional di-vide, which is difficult to cross in a debate context. Dockery’s variations provide a means of at least understanding the divide and the positions that differ from one’s own. To that aim, I present Dockery’s variations as a vital component for all attempts at dialogue in the inerrancy debate.